The Training Needs of Unit Trust Agents of a Selected Fund Management Company - Lim, Tian Poh (1999)
The main aim of the research was to determine to what extent training need exists among the Unit trust agent, and which area of job related knowledge, skill, attitude deserve emphasis In a training program It also aimed to determine the training need of the agency leaders and which area of key task needed to be stressed In a training program in this study, training need of Unit trust agents and agency leaders were identified and described one hundred and forty-five of the Unit trust agents and 73 agency leaders took part in this survey Data were collected via a need assessment questionnaire, which required among others, a rating by the unit trust agents of the proficiency level of Unit trust agents on 22 knowledge Items, 13 skill Items, and the relevance of these Items to the Job of the Unit trust agents As for the agency leaders, they were required to rate their proficiency level of 14 key tasks, and the relevance of these tasks to the job of agency leader. Attitude of the unit trust agents towards the customer, selling job, company and product was assessed based on the agreement of the respondents towards 12 attitude statements In relation to the customer, selling Job, company and product The result were descriptions of training needs in knowledge and skill for unit trust agents and key task training need for agency leaders the result included the overall degree of training need, the degree of training need, the ranking order of training need to training Importance In knowledge and skill for unit trust agents, and In key tasks for the agency leaders The description of attitude training for the unit trust agents was Inferred from the level of attitude, which IS high, moderate or low towards the customer, selling Job, company and product.